Improved understanding of drought controls on seasonal variation in Mediterranean forest canopy CO2 and water fluxes through combined in situ measurements and ecosystem modelling - Keenan, T; Garcia, R; Friend, A D; Zaehle, S; Gracia, C; Sabate, S (BIOGEOSCIENCES, 2009)
Water stress is a defining characteristic of Mediterranean ecosystems, and is likely to become more severe in the coming decades. Simulation models are key tools for making predictions, but our current understanding of how soil moisture controls ecosystem functioning is not sufficient to adequately constrain parameterisations. Canopy-scale flux data from four forest ecosystems with Mediterranean-type climates were used in order to analyse the physiological controls on carbon and water flues through the year. Significant non-stomatal limitations on photosynthesis were detected, along with lesser changes in the conductance-assimilation relationship. New model parameterisations were derived and implemented in two contrasting modelling approaches. The effectiveness of two models, one a dynamic global vegetation model ({''}ORCHIDEE{''}), and the other a forest growth model particularly developed for Mediterranean simulations ({''}GOTILWA+{''}), was assessed and modelled canopy responses to seasonal changes in soil moisture were analysed in comparison with in situ flux measurements. In contrast to commonly held assumptions, we find that changing the ratio of conductance to assimilation under natural, seasonally-developing, soil moisture stress is not sufficient to reproduce forest canopy CO2 and water fluxes. However, accurate predictions of both CO2 and water fluxes under all soil moisture levels encountered in the field are obtained if photosynthetic capacity is assumed to vary with soil moisture. This new parameterisation has important consequences for simulated responses of carbon and water fluxes to seasonal soil moisture stress, and should greatly improve our ability to anticipate future impacts of climate changes on the functioning of ecosystems in Mediterranean-type climates.
APS
Keywords: ecosystem functioning; forest ecosystems; Mediterranean; water stress

Effects of elevated CO2 and decreased water availability on holm-oak seedlings in controlled environment chambers - López, B; Sabate, S; Ruiz, I; Gracia, C (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
In Mediterranean ecosystems, water is an important limiting factor for plant growth. In addition to the increase in atmospheric CO2, some models predict increased drought in Mediterranean areas as a consequence of global change. Thus, to determine how increased atmospheric CO2 interacts with increased water stress and affects Mediterranean plant growth is an important achievement. The present study analyses how helm oak (Quercus ilex L.) seedlings are affected by both elevated CO2 and increased water stress. The CO2 concentrations were supplied in controlled environment chambers (350 and 500 ppm CO2), and water stress was performed according to a Mediterranean pattern (Potential Evapotranspiration to Rainfall ratio). The increased water stress was attained by watering half of the Mediterranean reference pattern. Results show that the positive effects of elevated CO2 on photosynthesis and growth are counteracted by increased water stress.
Keywords: CO2; controlled environment chambers; Quercus ilex